Correlation between the mantle and heterochronous crustal materials in the composition of Transbaikalia A-type granitoides: petrological and geodynamical implications - A. A. Tsygankov; V. B. Khubanov; G. N. Burmakina; A. L. Elbaev; V. V. Burdukovsky (Геодинамика и тектонофизика)
Late Paleozoic and Early Mesozoic alkaline A-type granitoids (anhydrous, alkaline, moderately aluminous, ferruginous) are widely distributed in the structures of the Central Asian Fold Belt. In Northern Mongolia and Transbaikalia, there are hundreds of massifs that formed from the end of the Permian to the Middle Jurassic inclusive. These massifs are composed of alkaline granites, alkaline and alkali-feldspar syenites, and located within crustal blocks (terranes) of different ages and origins. New geochemical data obtained for the Kruchininsky, Sherbakhtinsky, Shabartay and Khamney massifs, as well as earlier published materials (Bryansk and Kharitonovo plutons), demonstrate that despite the general petrogeochemical similarity of the main rock types composing these plutons, their isotopic composition (Nd) differs significantly. Our studies suggest that the isotopic composition of Transbaikalia A-type granitoids is caused, on the one hand, by the crust permeability for mantle magmas and, on the other hand, by the material heterogeneity of the crustal magma sources themselves, varying from the Early Precambrian crystalline blocks to ‘young’ island-arc terranes.